2017
DOI: 10.3889/oamjms.2017.180
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Effect of Aggressive Beverage on the Damage of Enamel Structure

Abstract: BACKGROUND:Dental erosion is a common problem in modern societies, owing to the increased consumption of acid drinks such as soft drinks, sports drinks, fruit juice. Examining the enamel surface with the Atomic Force Microscopy (AFM) enables more precise registering and defining the changes of enamel surface structure and microhardness. This method can be used to compare the efficiency of application of different preventive and therapy materials and medicaments in dentistry. The chronic regular consumption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…Oral infections represent an important concern in dentistry and many efforts are being made to contrast bacterial colonization [ 24 , 25 ]. In addition to infection of the teeth by cariogenic bacteria resulting in both primary [ 26 ] and secondary [ 27 ] decay, even tooth-supporting tissues can be jeopardized in susceptible patients by pathogenic microorganisms causing a dysbiosis leading to periodontitis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral infections represent an important concern in dentistry and many efforts are being made to contrast bacterial colonization [ 24 , 25 ]. In addition to infection of the teeth by cariogenic bacteria resulting in both primary [ 26 ] and secondary [ 27 ] decay, even tooth-supporting tissues can be jeopardized in susceptible patients by pathogenic microorganisms causing a dysbiosis leading to periodontitis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other drinks, Coca-Cola™ caused a more significant loss of P from the tooth ( Figure 1 ). Lutovac et al [ 34 ], examining the enamel surface with Atomic Force Microscopy (AFM), observed enamel surface structure and microhardness changes after an exposure time of 5 min in Coca-Cola™. According to Yuan et al [ 35 ], using an in situ study, the percentages of surface microhardness change on each exposure time (four days) due to demineralization.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the frequency of consumption of soft drinks by the individual, the amount of time the drink is retained in an individual's oral cavity, their general lifestyle and dietary habits, personal habits, systemic conditions. acidity, and ion concentration (aas et al, 2005, 2008) literature reveals that there exists a positive relationship between caries, dental erosion and the consumption of soft drinks (Badra et al, 2005;Hemingway et al, 2006;Barbour and shellis, 2007;lutovac et al, 2017). accordingly, the clinical manifestations and diagnosis of diseases caused by soft drinks should be regarded as a combination of erosion and caries, and clinicians should pay more attention to it.…”
Section: Methodsmentioning
confidence: 99%